Early Term Deliveries and the Risk of Pediatric Obstructive Sleep Apnoea in the Offspring. Issue 2 (9th February 2017) - Walfisch, Asnat; Wainstock, Tamar; Beharier, Ofer; Landau, Daniella; Sheiner, Eyal
Abstract: Background: Preterm delivery may affect the development of the upper airways resulting in a higher risk of obstructive sleep apnoea (OSA). We investigated whether children born at early term (37‐38 6/7 weeks' gestation) are at an increased risk for childhood OSA as compared with those born later. Methods: In this population‐based cohort analysis all singleton deliveries occurring between 1991–2013 at a single regional tertiary medical centre were included. Gestational age upon delivery was sub‐divided into: early preterm (<33 6/7 weeks' gestation), late preterm (34‐36 6/7), early term, full term (39‐40 6/7), late term (41‐41 6/7), and post term (>42 0/7). Incidence of OSA related hospitalizations of the offspring, up to the age of 18 years, was evaluated. A survival curve and a Cox model were used to assess the association. Results: During the study period 240 953 deliveries met the inclusion criteria. OSA hospitalization ( n = 1320) rates decreased as gestational age increased from 1.1% in the early preterm group, 0.8% in late preterm, 0.7% at early term, 0.5% in full term, 0.4% in late term, to 0.3% in post term born children. In the Cox regression, early term delivery exhibited an increased risk for paediatric OSA (adjusted hazard ratio (HR) 1.3 95% Confidence interval (CI) 1.2, 1.5) while late and post term deliveries were associated with significantly lower OSA risk when compared with full term (HR 0.8 95% CI 0.6, 0.9 and HR 0.6 95% CI 0.4, 0.8, respectively). Conclusions: Early term deliveries are associated with higher rates of paediatric OSA, which decrease gradually as gestational age advances.